Bahayanihan a campaign to promote the easy, affordable and sustainable ways of producing food for urban families of Metro Manila - Andres, Gervin Angelo A.; San Valentin, Marc (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Urban Agriculture, the practice of growing food in the cities, plays an important role in achieving food security and sustainability among Filipino urban families. Ever since, the practice of agriculture has become an integral part of human life. Through the course of its development, different challenges greatly affected the ways humans interact with its environment such as the rise of population, industrialization, and eventually, urbanization. This has led to problems the agriculture industry faces today including urban sprawls and land conversions, environment problems due to conventional farming practices, which also affected the health of the farmers as well as the consumers, and the decreasing numbers of Filipino farmers due to the outmigration of rural youth from agricultural communities. Likewise, securing food for the families becomes a challenge as urban population continues to grow. Findings in the research showed that indeed, urban agriculture can be a sustainable practice of providing safe and nutritious food for the urban families. Although, it was also observed that most of the people who practices agricultural activities in the urban were adults and the elders, and still, the sustained practice of agriculture unto the younger generations is still at risk since only a few were eager to engage with the activity. Thus, this thesis aims to promote Urban Farming to the urban families not only to start a sustainable practice of providing affordable, safe, and nutritious food within reach, but for the sustained practice of agriculture to the younger generations as well.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 136-138.
Keywords: Urban agriculture -- Philippines; Agriculture -- Philippines